Comparison of biomechanical characteristics for the skill level in cycle pedaling - Lee, G.-H.; Kim, J.-J.; Kang, S.-S.; Hong, A.-R.; So, J.-M. (Korean Journal of Sport Biomechanics, 2016)
Objective: This study aimed to compare biomechanical data between elite and beginner cyclists during cycle pedaling by performing a comparative analysis and to provide quantitative data for both pedaling performance enhancement and injury prevention. Methods: The subjects of this study included 5 elite cyclists (age: 18 ± 0 years, body mass: 64.8 ± 9.52 kg, height: 173.0 ± 4.80 cm) and 5 amateur cyclists (age: 20 ± 0 years, mass: 66.6 ± 2.36 kg, height: 175.6 ± 1.95 cm). The subjects pedaled on a stationary bicycle mounted on rollers of the same gear (front: 50 T and rear: 17 T = 2.94) and cadence of 90. The saddle height was adjusted to fit the body of each subject, and all the subjects wore shoes with cleats. In order to obtain kinematic data, 4 cameras (GR-HD1KR, JVC, Japan) were installed and set at 60 frames/sec. An electromyography (EMG) system (Telemyo 2400T, Noraxon, USA) was used to measure muscle activation. Eight sets of data from both the left and right lower extremities were obtained from 4 muscles (vastus medialis oblique [VMO], vastus lateralis oblique [VLO], and semitendinosus [Semitend], and lateral gastrocnemius [Gastro]) bilaterally by using a sampling frequency of 1,500 Hz. Five sets of events (0°, 90°, 180°, 270°, and 360°) and 4 phases (P1, P2, P3, and P4) were set up for the data analysis. Imaging data were analyzed for kinematic factors by using the Kwon3D XP computer software (Visol, Korea). MyoResearch XP Master Edition (Noraxon) was used for filtering and processing EMG signals. Results: The angular velocity at 360° from the feet was higher in the amateur cyclists, but accelerations at 90° and 180° were higher in the elite cyclists. The amateur cyclists had greater joint angles at 270° from the ankle and wider knee joint distance at 0°, 180°, and 360° than the elite cyclists. The EMG measurements showed significant differences between P2 and P4 from both the right VLO and Semitend. Conclusion: This study showed that lower body movements appeared to be different according to the level of cycle pedaling experience. This finding may be used to improve pedaling performance and prevent injuries among cyclists.